Boro/carbothermal reduction synthesis of uranium tetraboride and its oxidation behavior in dry air. Issue 3 (20th August 2018) - Guo, Hangxu; Wang, Jieru; Chen, Denglei; Tian, Wei; Cao, Shiwei; Chen, Desheng; Tan, Cunmin; Deng, Qihuang; Qin, Zhi
Abstract: Uranium tetraboride (UB4 ) was successfully synthesized by boro/carbothermal reduction of UO2 with B4 C and carbon as combined reduction agents under flowing argon. The effects of processing temperature and mole ratios of starting materials on phase evolution were studied. XRD results demonstrated that UB4 was obtained with 3.75 mol% B4 C in excess based on the UO2 /B4 C/C molar ratios of 1:1:1 at 1500°C. SEM observation revealed that submicrometer‐sized quasi‐spherical UB4 particles cemented together to be an aggregate. The laser particle size analysis showed that the particle size was in the range of 1‐10 μm. The oxidation behavior of UB4 was also investigated by TG and XRD. The oxidation of UB4 started at about 500°C and it showed better oxidation resistance than other basic uranium nuclear fuels (UO2, UC, UN and U3 Si2 ). The oxidation chemical process of UB4 was presented as a three‐step process: (a) the formation of U3 O8 and B2 O3 oxidation products; (b) the formation of UB2 O6 intermediate product by the interaction of U3 O8 and B2 O3 ; (c) the decomposition of UB2 O6 to get U3 O8 .